The impact of special drills using the overlapping station method on developing certain offensive skills and performance endurance for under-18 basketball players - Raouf, L.Dr. Rizkar Mohammed; Mahmoud, L.Dr. Raheeq Nizar; Salman, Asst.L.Hanin Safaa (Sulaimani Journal for Humanities, 2026)
This research aimed to develop station-based training exercises to enhance the offensive skills and performance endurance of young female basketball players. An experimental design with two groups (experimental and control) was employed, deemed most suitable for the research problem. The sample consisted of young female players (under 18 years old) from the North Gas Club in Sulaymaniyah Governorate, Iraq, serving as the experimental group, and the Halabja Club as the control group, with six players in each group. The mean scores for the research sample in terms of height, weight, chronological age, and training age were 170.41 ± 4.42 cm, 58.98 ± 2.28 kg, 15.96 ± 0.81 years, and 7.25 ± 0.75 years, respectively. Two pilot experiments were conducted: the first to establish the scientific criteria for the research tests, and the second to implement the training program. This was followed by a pre-test, the main research experiment, and then the post-tests. The experimental program was implemented for eight weeks, with four training sessions per week. The statistical package SPSS version 26 was used to obtain the research results. The study concluded that the program led to a significant improvement in offensive skills and performance endurance. It is important to focus on engaging station-based training exercises to develop the physical attributes of young female basketball players, as well as to emphasize interactive exercises in offensive skills training, which enables coaches to develop the physical attributes specific to performance
Keywords: Basketball; station style; physical attributes; training of young women; special exercises